Electrochemical Study of Esculetin Nitration by Digital Simulation of Cyclic Voltammograms - Lida Khalafi; Mohammad Yari; Farzaneh Yadaei; Shabnam Majidzade (Journal of Chemistry)
The reaction of electrochemically generated o-quinones from oxidation of esculetin as Michael acceptor with nitrite ion as nucleophile has been studied using cyclic voltammetry. The reaction mechanism is believed to be EC, including oxidation of catechol moiety of esculetin followed by Michael addition of nitrite ion. The observed homogeneous rate constants (𝑘obs) for reactions were estimated by comparing the experimental voltammetric responses with the digitally simulated results based on the proposed mechanism. Also the effects of pH and nucleophile concentration on voltammetric behavior and the rate constants of chemical reactions were described.